SOCIO-ECONOMIC IMPACT OF ENTERPRENEURIAL SPIRIT OF WOMEN IN SUB-SAHARA AFRICA: A CASE OF TEENAGE HEADPORTER IN GHANA. - Liu, Ruiwen; Duduchoge, Solomon (IJRDO - Journal of Social Science and Humanities Research, 2017)
It is seen that child labour with regards to the head porterage business in Ghana is predominantly made up of people from the three northern regions of Ghana. Many of them are from the rural areas who migrate to the two larger cities of Kumasi and Accra in Ghana and use themselves as means of transport to carry wares of clients as well as commuters. The head porters as street children are clearly within the low income earning category, however, they exhibit a high degree of determination to succeed in their chosen career. Despite the fact that earnings in this occupation are low, those pursuing this occupation arrange their living arrangements so as to maximize their savings. The rigors of the occupation, the low income and the degree of overcrowding associate d with the businessoften lead them into contracting diseases and pregnancies. Institutions such as governmental and non-governmental are educating, counselling and impacting vocational skills to the children in order to rehabilitate them.